2017
DOI: 10.3892/ol.2017.7323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histological, immunohistochemical and genetic factors associated with measurable response of high‑risk canine mast cell tumours to tyrosine kinase inhibitors

Abstract: The aim of the present prospective-retrospective study was to evaluate the response of high-risk canine mast cell tumours (MCTs) to tyrosine kinase inhibitors (TKIs) and to correlate this with prognostic factors. A total of 24 dogs presented with macroscopic cutaneous MCTs at disease stage II or III, and therefore, at high-risk of associated mortality, were included in the study and treated with masitinib (n=20) or toceranib (n=4). A total of 12/24 dogs achieved an objective response and the overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The original TOC studies demonstrated higher response rates for c‐kit mutated tumours, but did not report an increased PFI for this cohort: long‐term comparison of dogs receiving TOC and dogs receiving placebo was not carried out, as dogs in the placebo group were eligible to join the treatment group after 6 weeks. Subsequent studies looking at small cohorts of dogs treated with TOC have suggested that c‐kit mutation status may not be of value in predicting prognosis, or may be a negative prognostic indicator . Interestingly, although mitotic index was the sole predictor of PFI on multivariate analysis, pKIT was the sole predictor of OST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original TOC studies demonstrated higher response rates for c‐kit mutated tumours, but did not report an increased PFI for this cohort: long‐term comparison of dogs receiving TOC and dogs receiving placebo was not carried out, as dogs in the placebo group were eligible to join the treatment group after 6 weeks. Subsequent studies looking at small cohorts of dogs treated with TOC have suggested that c‐kit mutation status may not be of value in predicting prognosis, or may be a negative prognostic indicator . Interestingly, although mitotic index was the sole predictor of PFI on multivariate analysis, pKIT was the sole predictor of OST.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the studies evaluating TOC did not report the effect of c‐kit mutation on PFI, and the studies evaluating masitinib did not report the effect of c‐kit mutation on response to treatment. Furthermore, other studies have failed to demonstrate a relationship between c‐kit mutation status and outcome or have even demonstrated a negative relationship between mutation status and outcome following TOC treatment . Thus, additional study of the utility of activation status of the KIT receptor and other factors to predict outcome of canine MCT patients following TKI treatment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have sought to evaluate the significance of the presence of activating c‐kit mutations and/or aberrant KIT protein localization on postsurgical outcome in dogs with MCT . Furthermore, some studies have begun to evaluate whether these factors may affect outcome with medical therapy, specifically with TKIs . The goal of this review is to summarize the available data regarding the utility of c‐kit gene mutation and KIT protein localization as prognostic and predictive tests for canine MCT.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was made in a small number of dogs treated with the KIT TKI imatinib; dogs with c‐kit exon 11 ITDs were numerically more likely to experience objective responses to imatinib, although long‐term outcomes were not reported . However, some recent studies have suggested no correlation between TKI response and c‐kit mutational status …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation